(untitled) (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
Paddy rice farming is a source of income and employment opportunities for rural communities, therefore it is necessary to have proper management using production factors efficiently. Inefficient use of production factors in lowland rice farming will result in low production and high costs, and ultimately reduce farmers’ income. For farmers, farming activities carried out are not only increasing production but how to increase income through the use of production factors, because the addition of production factors often does not provide the income expected by farmers. The purpose of this study was to determine the income of lowland rice farmingd in Toribulu Village, Toribulu District, Parigi Moutong Regency. The location of this study was chosen purposively with the consideration that Toribulu Village is one of the rice fields producing areas in Toribulu District, Parigi Moutong Regency. The research was conducted for 3 months, from October to December 2019. Respondents in this study were rice farmers in Toribulu Village, Toribulu District. Determination of respondents in this study using simple random sampling method (Simple Random Sampling), that is, from all respondents taken in this study were 32 respondents of lowland rice farmers. from a population of 125 rice farmers. 32 respondents were taken based on the Slovin formula and with the consideration that most of the farmers in Toribulu Village are lowland rice farmers so that the 32 respondents of lowland rice farmers can represent the population of lowland rice farmers in Toribulu Village. The data used in this study are primary data and secondary data. The data analysis used is income analysis.The results showed that the average lowland rice production by lowland rice farmers in Toribulu Village was 3,163 kg / Ha with an average income of Rp. 28,462,500 / Ha / MT, while the average total costincurred by lowland rice farmers is Rp. 10,925,593 / Ha / MT so that the income obtained by rice farmers is Rp. 17,536,907 / Ha / MT.